Kuat Lentur Beton Menggunakan Agregat Batu Petangis dan Pasir Semboja dengan Penambahan Botol Plastik - Topik Wahyu Widianto; Andi Marini Indriani; Gunaedy Utomo (Kadiri University, 2023)
Utilizing local materials is a strategic step in optimizing concrete production in East Kalimantan. There's an example supply of petangis stone and semboja sand aggregates. Apart from that, using various wastes, including plastic waste, in concrete production is also a current issue. This study aims to investigate the potential substitution of fine aggregates with PET and combine them with local materials, to understand their impact on the bending strength of concrete. The study tested concrete bending strength using 15x15x60 cm blocks with PET plastic substitutions at 0.30%, 0.45%, and 0.60% of sand weight, comparing them with PET-free concrete. The research results show that adding 0.30 and 0.45% PET plastic bottles causes a decrease in the flexural strength of concrete. This is related to the influence of changes in the composition of the concrete mix, including factors such as uneven aggregate distribution and less-than-optimal material binding. Flexural strength increases at a percentage of 0.60% by 3.7% or 3.3 MPa and shows better results than normal concrete. So the PET percentage can be used as a recommendation in making concrete using local materials such as petangis stone aggregate and semboja sand.